A study on etiologic agents and clinical manifestations of dermatophytosis in Yazd, Iran - Sara Rashidian; Mehraban Falahati; Parivash Kordbacheh; Mahmoud Mahmoudi; Mahin Safara; Hossein Sadeghi Tafti; Shahram Mahmoudi; Farideh Zaini (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Dermatophytosis is one of the most common infections of skin, hair, and nails, caused by a group of keratinophilic fungi known as dermatophytes. Species identification of these fungi is of great significance from epidemiological and therapeutic points of view. The objective of the present study was to investigate dermatophytosis and its causative agents in patients, referring to the Central Mycology Laboratory of Yazd University of Medical Sciences, Yazd, Iran. Materials and Methods: In total, 139 clinically suspected cases of dermatophytosis were examined during 12 months from February 2014 to February 2015. Skin scrapings were assessed through direct microscopic examinations and culture studies. Dermatophyte isolates were identified based on colony morphology on potato dextrose agar and dermatophyte test medium, nutritional requirements, urease and hair perforation tests, and microscopic characteristics on slide cultures. Results: Dermatophytosis was mycologically confirmed in 26 (18.70%) out of 139 cases. Although there was a statistically insignificant difference between male and female subjects, men were dominantly affected. Infection was significantly common in the age group of ≤ 29 years (P<0.043). The most common clinical manifestation of dermatophytosis was tinea corporis (69.2%), followed by tinea cruris (15.4%), tinea manuum (11.5%), and tinea pedis (3.8%). Trichophyton mentagrophytes complex was the main etiologic agent (38.5%), followed by T. rubrum (23%), T. violaceum (15.5%), T. verrucosum (11.5%), Microsporum canis (7.7%), and Epidermophyton floccosum (3.8%). Conclusion: In comparison with previous research, epidemiology of dermatophytosis has changed in Yazd over the past decades. Therefore, periodical investigations on the epidemiological aspects of this infection are required for efficient control and prevention of this cutaneous dermatophytic disease.